2016
DOI: 10.15171/hpp.2015.031
|View full text |Cite
|
Sign up to set email alerts
|

An Advertisement and Article Analysis of Skin Products and Topics in Popular Women’s Magazines: Implications for Skin Cancer Prevention

Abstract: Background: In the United States, skin cancer is the most commonly diagnosed cancer, with an estimated 5 million people treated per year and annual medical treatment expenditures that exceed 8 billion dollars. The purpose of this study was two-fold: 1) to enumerate the number of advertisements for skin products with and without Sun Protection Factor (SPF) and to further analyze the specific advertisements for sunblock to determine if models, when present, depict sun safe behaviors and 2) to enumerate the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Characteristics of the readership of each magazine were obtained from online media kits containing annual readership statistics and demographics, including median age and median household income, and are described in detail elsewhere. [ 8 ] Median age was grouped as ≤21, 22–30, 31–40, and ≥40 years to correspond with standardized age groupings for young adolescent, young adult, adult, and middle-aged adult, respectively. Using the national median for annual household income, median household income of the readership was dichotomized at or below and greater than the national median of $51,939.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of the readership of each magazine were obtained from online media kits containing annual readership statistics and demographics, including median age and median household income, and are described in detail elsewhere. [ 8 ] Median age was grouped as ≤21, 22–30, 31–40, and ≥40 years to correspond with standardized age groupings for young adolescent, young adult, adult, and middle-aged adult, respectively. Using the national median for annual household income, median household income of the readership was dichotomized at or below and greater than the national median of $51,939.…”
Section: Methodsmentioning
confidence: 99%
“…Using a coding sheet adapted from the previous studies of magazine analysis,[ 8 ] the characteristics of advertisements in this sample of magazines were gathered. Magazines were purchased and advertisements were enumerated and categorized based on the product or service highlighted.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies indicated that appearance dissatisfaction and tanning intentions strongly associated with social media use [18,21]. Current literature regarding social media [18,22] is consistent with research on traditional media in that images are often pro-tan and lack focus on skin cancer prevention [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 71%